Morfometria do trato vocal por ressonância magnética: simulação de padrões patológicos articulatórios - Sandra M. Rua Ventura (2014)
Introduction - The shape or morphologic analysis of anatomical structures, such as the vocal tract can be performed from two-dimensional (2D) or volumetric acquisitions (3D) of magnetic resonance imaging (MRI). This imaging technique has had an increasing use in the study of speech production. Objectives - To determine a method to perform the morphometric analysis of the vocal tract from magnetic resonance imaging; to present anatomical patterns during the normal speech production of some vowels and two pathological articulatory disorders in simulated context. Methods - The image data was collected from 2D (Turbo Spin Echo) and 3D (Flash Gradient Echo) acquisitions of MRI of four subjects during the production of three vowels; in addition, two articulatory disorders were assessed using this imaging protocol. The morphology of the vocal tract was extracted using manual and automatic techniques of image processing and analysis. Results - Based on five articulatory measurements, it was possible to study the entire vocal tract during vowel production, including the position and shape of the articulators involved. Based on these measurements, it was possible to identify the strategies most commonly adopted in the production of each sound, including the articulatory posture and the modification of each measure for the subjects under study. Concerning the voices of the different speakers, the variability in the assessed volumes of the vocal tract for each sound was found, and in particular, the increased vocal tract volume in the articulatory disorder - the sigmatism. Conclusion - MRI is a promising technique for speech production studies, safe, non-invasive and that provides reliable information concerning the morphometric analysis of the vocal tract.